Composition

By using alkaline soluble materials and compositions with fluoride -containing compounds with cross -linking bases, the problem of forming high -resolution, pattern solidified membrane at lower temperature conditions is solved. High contrast.

CN119365821APending Publication Date: 2025-01-24MERCK PATENT GMBH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380045555.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-07
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to form high resolution, patterned cured films under lower temperature conditions, while environmental friendliness and contrast maintenance challenges.

Method used

A composition containing an alkali-soluble material and a fluorine-containing compound with a cross-linking group is used to form a cured film through coating and heating processes, and a low-concentration alkaline developer is used during the development process.

Benefits of technology

The formation of high -resolution and pattern curing film is formed under lower temperature conditions, which improves environmental friendship and maintains high contrast.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174679100000261
    Figure BDA0005174679100000261
Patent Text Reader

Abstract

A composition containing an alkali-soluble material, a cured film, and a method for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition containing an alkali-soluble material, a method for producing a cured film using the composition, a cured film formed by the method, a photoconversion device including the cured film, and a display device including the photoconversion device. Background Art

[0002] The black matrix for color filters used in color display devices is to mix a light-shielding black pigment such as carbon black with an alkali-soluble resin to form a resist composition, which is coated, exposed and developed to form a pattern. The black matrix is ​​used, for example, in a liquid crystal display element to prevent light leakage from non-converted pixels and maintain high contrast. In addition, amorphous silicon and oxide semiconductors will generate leakage current due to light excitation when exposed to light, so the light directed to the thin film transistor portion is shielded by a black matrix layer to suppress leakage current (patent document 1).

[0003] A photosensitive colored resin composition for forming a partition wall is proposed, the composition comprising a fluorine atom-containing resin having a crosslinking group as a liquid repellent (Patent Document 2).

[0004] In recent years, environmentally friendly compositions have been sought. For example, fluorine-containing compounds such as perfluoroalkyl substances (PFAS) have concerns about environmental pollution, and there is a demand to reduce their blending amount.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-203599

[0008] Patent Document 2: Japanese Patent No. 6885518 Summary of the invention

[0009] Technical Problems to be Solved by the Invention

[0010] The present inventors surprisingly found that there are one or more important issues that are expected to be improved as listed below.

[0011] Provided is a composition capable of forming a cured film, wherein the upper portion of the cured film exhibits oleophobicity and the lower portion exhibits oleophilicity;

[0012] Provided is a patternable composition for making a bank, which exhibits oleophobicity at the top of the bank and oleophilicity at the bottom of the bank;

[0013] Provided is a patternable composition, which preferably exhibits oleophobicity at the top of the partition wall and oleophilicity at the bottom of the partition wall and the side surface of the partition wall at the opening after being made into a partition wall;

[0014] Provided is a partition wall and / or a patternable composition for forming the partition wall, wherein the partition wall opening is oleophilic to ink, preferably the partition wall opening can be filled with ink without gaps, and the partition wall top is oleophobic to ink, preferably the partition wall top can appropriately repel ink, wherein the ink is preferably a quantum dot ink, more preferably the ink is an ink containing an acrylic monomer, and further preferably the ink is solvent-free;

[0015] Provided is a composition that can be cured and patterned at a lower temperature than conventional compositions;

[0016] Provided is a composition comprising a pigment that does not adversely affect patterning, preferably a black pigment;

[0017] Providing a composition that can be patterned at high resolution;

[0018] Provided is a composition that can achieve a thicker film as a partition material for a display device;

[0019] Provided is a composition which can achieve a thicker film as a partition material of a display device and preferably contains a black pigment;

[0020] Providing an environmentally friendly composition;

[0021] Provided is a composition which is environmentally friendly and can be developed by a low-concentration alkaline developer other than an organic developer.

[0022] Solutions for solving technical problems

[0023] The present inventors have conducted intensive research and found a composition comprising (I) an alkali-soluble material and (II) a fluorine-containing compound having a crosslinking group.

[0024] The mass ratio of the content of the component (II) to the content of the component (I) ((II) / (I)) is 0.0000005 to 0.01.

[0025] In another aspect, the present invention relates to a method for producing a cured film, comprising:

[0026] A step of applying the composition to a substrate to form a coating film; and

[0027] A step of heating the coating film.

[0028] In another aspect, the present invention relates to a cured film produced or producible by the above method.

[0029] In another aspect, the present invention relates to a cured film comprising an alkali-soluble material and a polymer derived from a fluorine-containing compound having a crosslinking group.

[0030] In another aspect, the present invention relates to a photoconversion device including the above-mentioned cured film.

[0031] In another aspect, the present invention relates to a display device including the above-mentioned cured film or the above-mentioned photoconversion device.

[0032] Effects of the Invention

[0033] According to the present invention, one or more of the following effects can be expected.

[0034] Provided is a composition capable of forming a cured film, wherein the upper portion of the cured film exhibits oleophobicity and the lower portion exhibits oleophilicity;

[0035] Provided is a patternable composition for making a partition wall, which exhibits oleophobicity at the top of the partition wall and oleophilicity at the bottom of the partition wall;

[0036] Provided is a patternable composition, which preferably exhibits oleophobicity at the top of the partition wall after being made into a partition wall, and exhibits oleophilicity at the bottom of the partition wall and the side surface of the partition wall at the opening;

[0037] Provided is a partition wall and / or a patternable composition for forming the partition wall, wherein the partition wall opening is oleophilic to ink, preferably the partition wall opening can be filled with ink without gaps, and the partition wall top is oleophobic to ink, preferably the partition wall top can appropriately repel ink, wherein the ink is preferably an ink containing quantum dots, more preferably an ink containing acrylic monomers, and further preferably the ink is solvent-free;

[0038] Provided is a composition that can be cured and patterned at a lower temperature than conventional compositions;

[0039] Provided is a composition comprising a pigment that does not adversely affect patterning, preferably a black pigment;

[0040] An environmentally friendly composition is provided. DETAILED DESCRIPTION

[0041] More advantages of the present invention will become more apparent from the following detailed description. However, the above summary and the following detailed description are only used to illustrate the present invention and are not intended to limit the invention of the claims.

[0042] [definition]

[0043] In this specification, unless otherwise specified, symbols, units, abbreviations, and terms have the following meanings.

[0044] In this specification, unless otherwise specified or mentioned, the singular includes the plural, and "one" or "it" means "at least one". In this specification, unless otherwise specified, a certain concept element can be expressed in plural types, and when its amount (such as mass % or molar %) is recorded, its amount means the sum of these plural types. "And / or" includes all combinations of elements, and also includes the use of individual individuals.

[0045] In the present specification, when "to" or "-" is used to express a numerical range, these include both endpoints and the unit is the same. For example, 5 to 25 mol% means 5 mol% or more and 25 mol% or less.

[0046] In this specification, according to common technical knowledge, (meth)acrylate refers to acrylate, methacrylate, or a mixture of acrylate and methacrylate.

[0047] In the present specification, a monomer refers to a monomeric substance, which is a monomer that can form a polymer (including an oligomer) by reacting with other monomers.

[0048] In the present specification, the polymer may be in the form of an oligomer. The mass average molecular weight of the polymer is not particularly limited, but is preferably 1,000 to 100,000, and more preferably 2,000 to 30,000. The mass average molecular weight refers to the polystyrene-equivalent mass average molecular weight measured by gel permeation chromatography.

[0049] In the present specification, an alkyl group refers to a group obtained by removing any one hydrogen from a straight-chain or branched saturated hydrocarbon, and includes straight-chain alkyl groups and branched alkyl groups. A cycloalkyl group refers to a group obtained by removing one hydrogen from a saturated hydrocarbon including a cyclic structure, and includes a straight-chain or branched alkyl group as a side chain in the cyclic structure as required.

[0050] In this specification, an aryl group refers to a group obtained by removing any one hydrogen atom from an aromatic hydrocarbon. An alkylene group refers to a group obtained by removing any two hydrogen atom from a linear or branched saturated hydrocarbon. An arylene group refers to a hydrocarbon group obtained by removing any two hydrogen atom from an aromatic hydrocarbon.

[0051] In this manual, “C x~y ”, “C x ~C y ” and “C x " refers to the number of carbon atoms in a molecule or a substituent. For example, C 1~6Alkyl refers to an alkyl group having 1 or more and 6 or less carbon atoms (methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.). In addition, the fluoroalkyl group in this specification refers to an alkyl group in which one or more hydrogen atoms are replaced by fluorine atoms, and the fluoroaryl group refers to an aryl group in which one or more hydrogen atoms are replaced by fluorine atoms.

[0052] In the present specification, when a polymer has a plurality of repeating units, these repeating units are copolymerized, and these copolymerizations are any of alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, or a mixture thereof.

[0053] In this specification, % means mass % and ratio means mass ratio.

[0054] In this specification, the unit of temperature is Celsius. For example, 20 degrees means 20 degrees Celsius.

[0055] The additive refers to a compound having a certain function (for example, if it is a base generator, it is a compound that generates a base). The compound may also be dissolved or dispersed in a solvent and added to the composition. As one embodiment of the present invention, such a solvent is preferably a solvent (V) or is contained in the composition of the present invention as another component.

[0056] <Composition>

[0057] The composition of the present invention comprises (I) an alkali-soluble material and (II) a fluorine-containing compound having a crosslinking group.

[0058] In one embodiment of the present invention, the present invention consists essentially of (I) an alkali-soluble material and (II) a fluorine-containing compound having a cross-linking group.

[0059] In another embodiment of the present invention, the present invention consists of (I) an alkali-soluble material and (II) a fluorine-containing compound having a crosslinking group.

[0060] The composition of the present invention is preferably a film-forming composition, and more preferably a cured film-forming composition.

[0061] The composition of the present invention is preferably a photosensitive composition, and more preferably a negative photosensitive composition.

[0062] Preferably, the composition of the present invention further comprises (III) a colorant (preferably an organic colorant and / or an inorganic colorant, more preferably an organic and / or inorganic black colorant), (IV) a polymerization initiator, and / or (V) a solvent.

[0063] The composition of the present invention can exhibit better effects when forming a film of 100 μm or less, but is preferably a negative photosensitive composition for thick films that exhibits further effects when forming a thick film.

[0064] In the present invention, the film thickness is obtained by measuring the film thickness at 3 to 5 locations using a stylus-type surface profile measuring instrument manufactured by ULBAC Co., Ltd. and calculating the average value thereof.

[0065] The viscosity of the composition of the present invention is preferably 0.1 to 10,000 cP, more preferably 1.0 to 8,000 cP. Here, the viscosity is a viscosity measured at 25°C using a rotational viscometer.

[0066] (I) Alkali-soluble materials

[0067] The composition of the present invention contains (I) an alkali-soluble material (hereinafter sometimes referred to as (I) component; the same applies to other components).

[0068] The alkali-soluble material is an alkali-soluble monomer, an alkali-soluble polymer or a mixture thereof.

[0069] The alkali-soluble material preferably has a partial structure having an acid group. The acid group is preferably an acid group having an acid dissociation constant (pKa) of 7 or less, and more preferably -OH, -COOH, -SO 3 H.-OSO 3 H, -PO 3 H 2 ,-OPO 3 H 2 、-CONHSO 2 、-SO 2 NHSO 2 By having these acid groups (preferably carboxyl groups), the solubility of the alkali-soluble material in a low-concentration developer can be effectively improved.

[0070] When the alkali-soluble material is an alkali-soluble monomer, the alkali-soluble monomer is preferably a compound containing one or more (more preferably two or more) (meth)acryloyloxy groups. The alkali-soluble material is preferably a compound containing two or more (meth)acryloyloxy groups and / or an alkali-soluble polymer.

[0071] More preferably, the alkali-soluble material includes a compound containing two or more (meth)acryloyloxy groups, and further preferably, it further includes an alkali-soluble polymer.

[0072] Compounds containing two or more (meth)acryloyloxy groups

[0073] A compound containing two or more (meth)acryloyloxy groups is sometimes referred to as a compound containing (meth)acryloyloxy groups. Among them, (meth)acryloyloxy is a general term for acryloyloxy and methacryloyloxy groups. The compound is a compound that can react with an acryloyl group-containing compound, an alkali-soluble polymer, etc. to form a cross-linked structure. Here, in order to form a cross-linked structure, it must be a compound containing two or more acryloyloxy or methacryloyloxy groups as reactive groups. In order to form a higher-dimensional cross-linked structure, it is preferably a compound containing three or more acryloyloxy or methacryloyloxy groups.

[0074] As such a compound containing two or more (meth)acryloyloxy groups, esters obtained by reacting (α) a polyol compound having two or more hydroxyl groups with (β) two or more (meth)acrylic acids are preferably used.

[0075] Examples of the (α) polyol compound include compounds having a saturated or unsaturated aliphatic hydrocarbon, an aromatic hydrocarbon, a heterocyclic hydrocarbon, a primary amine, a secondary amine, a tertiary amine, an ether, etc. as a basic skeleton and having two or more hydroxyl groups as substituents. The polyol compound may also contain other substituents, such as a carboxyl group, a carbonyl group, an amine group, an ether bond, a thiol group, a thioether bond, etc., within the scope of not impairing the effects of the present invention.

[0076] As preferred polyol compounds, alkyl polyols, aryl polyols, polyalkanolamines, cyanuric acid, or dipentaerythritol can be listed. Here, when the (α) polyol compound has more than 3 hydroxyl groups, it is not necessary for all hydroxyl groups to react with (meth) acrylic acid, and it can also be partially esterified. That is, the esters can also have unreacted hydroxyl groups. As such esters, tris (2-acryloyloxyethyl) isocyanurate, dipentaerythritol hexa (meth) acrylate, tripentaerythritol octa (meth) acrylate, pentaerythritol tetra (meth) acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, polytetramethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, di (trimethylolpropane) tetraacrylate, tricyclodecane dimethanol diacrylate, 1,9-nonanediol diacrylate, 1,6-hexanediol diacrylate, 1,10-decanediol diacrylate, etc. can be listed. Among these, tris(2-acryloyloxyethyl)isocyanurate and dipentaerythritol hexaacrylate are preferred from the viewpoint of reactivity and the number of crosslinkable groups. In addition, in order to adjust the shape of the pattern formed, two or more of these compounds may be combined. Specifically, it is preferred to combine a compound containing three (meth)acryloyloxy groups with a compound containing two (meth)acryloyloxy groups.

[0077] From the viewpoint of reactivity, such a compound is preferably a molecule relatively smaller than the alkali-soluble polymer. Therefore, the molecular weight is preferably 2,000 or less, and more preferably 1,500 or less.

[0078] The content of the (meth)acryloyloxy-containing compound can be adjusted depending on the type of the polymer or acryloyloxy-containing compound used, but is preferably 5 to 90% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 70% by mass based on the total mass of the composition excluding the solvent.

[0079] When combined with an alkali-soluble polymer, the content of the (meth)acryloyloxy-containing compound is preferably 10 to 95% by mass, more preferably 30 to 90% by mass, and further preferably 50 to 80% by mass based on the total mass of the component (I) from the viewpoint of compatibility with the alkali-soluble polymer. These (meth)acryloyloxy-containing compounds may be used alone or in combination of two or more.

[0080] Alkali soluble polymer

[0081] As the alkali-soluble polymer, it is desirable to select a polymer which is soluble in an organic solvent such as propylene glycol monomethyl ether acetate (hereinafter referred to as PGMEA), is water-soluble, and is soluble in an alkaline developer before exposure.

[0082] The alkali-soluble polymer preferably has a structural part having an acid group, and more preferably is a polymer obtained by copolymerizing a structural part having an acid group and a structural part not having an acid group.

[0083] Here, as the acid group, an acid group having an acid dissociation constant (pKa) of 7 or less is preferred, and -OH, -COOH, -SO 3 H.-OSO 3 H, -PO 3 H 2 ,-OPO 3 H 2 、-CONHSO 2 、-SO 2 NHSO 2 By having these acid groups (preferably carboxyl groups), the solubility of the alkali-soluble polymer in a low-concentration developer can be effectively improved.

[0084] The alkali-soluble polymer (which may be in the form of an oligomer) used in the present invention preferably contains an acryloyl group.

[0085] Preferably, the alkali-soluble polymer is composed of a (meth) acrylic polymer, a siloxane polymer, a siloxane (meth) acrylic polymer, or a mixture thereof. In addition, the alkali-soluble polymer used in the present invention is not particularly limited, and is preferably selected from polysiloxanes containing siloxane bonds in the main skeleton and (meth) acrylic polymers. Among these, (meth) acrylic polymers are more preferably used from the viewpoint that they can be appropriately used in low-temperature processes. More preferably, acrylic polymers are used.

[0086] The alkali dissolution rate of the alkali-soluble polymer was measured and calculated as follows using a 0.03 mass % KOH (potassium hydroxide) aqueous solution as an alkali solution.

[0087] The alkali-soluble polymer was diluted to 35% by mass with PGMEA and dissolved while stirring for 1 hour at room temperature using a stirrer. In a clean room at a temperature of 23.0±0.5°C and a humidity of 50±5.0%, 1cc of the modulated alkali-soluble polymer solution was dropped onto the center of a 4-inch, 525μm thick silicon wafer using a pipette and spin-coated to a thickness of 2±0.1μm, and then the solvent was removed by heating on a hot plate at 100°C for 90 seconds. The film thickness of the coating was measured using a spectroscopic ellipsometer (JA Woollam).

[0088] Secondly, the silicon wafer with this film is quietly immersed in a 6-inch diameter glass petri dish adjusted to 23.0±0.1°C and added with 100ml of 0.03 mass% KOH aqueous solution, and then left to stand, and the time until the coating disappears is measured. The dissolution rate is calculated by dividing the time until the film disappears from the end of the wafer to the inside 10mm. In the case where the dissolution rate is significantly slow, the film thickness is measured after the wafer is immersed in the KOH aqueous solution for a certain period of time, and the change in film thickness before and after immersion is divided by the immersion time to calculate the dissolution rate. The above measurement method is performed 5 times, and the average value of the obtained values ​​is used as the dissolution rate of the alkali-soluble polymer.

[0089] The alkali-soluble polymer is preferably a polymer that dissolves and disappears in a 0.03 mass % KOH aqueous solution within 10 minutes at a portion of the coating film 10 mm inside the wafer edge in the above-mentioned measurement and calculation of the alkali dissolution rate.

[0090] (Polysiloxane)

[0091] Alkali soluble polymers may also include siloxane (Si-O-Si) bonds as the main skeleton. In the present invention, the polymer including siloxane bonds as the main skeleton is referred to as polysiloxane. The skeleton structure of polysiloxane can be divided into silicone skeleton (the number of oxygen atoms bonded to silicon atoms is 2), silsesquioxane skeleton (the number of oxygen atoms bonded to silicon atoms is 3), and silica skeleton (the number of oxygen atoms bonded to silicon atoms is 4) according to the number of oxygen bonded to silicon atoms. In the present invention, it may be any one of these. The polysiloxane molecule may also include a combination of a plurality of these skeleton structures. Preferably, the polysiloxane used in the present invention includes a silsesquioxane skeleton.

[0092] Polysiloxanes usually have silanol groups or alkoxysilyl groups. Such silanol groups and alkoxysilyl groups refer to hydroxyl groups and alkoxy groups directly bonded to the silicon forming the siloxane skeleton. Here, it is believed that silanol groups and alkoxysilyl groups, in addition to having the effect of promoting the curing reaction when using the composition to form a cured film, also contribute to the reaction with the silicon-containing compound described later. Therefore, polysiloxanes preferably have these groups.

[0093] (Acrylic polymer)

[0094] The acrylic polymer preferably used in the present invention can be selected from commonly used acrylic polymers, such as polyacrylic acid, polymethacrylic acid, polyalkyl acrylate, polyalkyl methacrylate, etc. As an example, the acrylic polymer used in the present invention preferably contains a repeating unit containing an acryloyl group, and the acrylic polymer preferably has a structural part having an acid group.

[0095] Here, as the acid group, an acid group having an acid dissociation constant (pKa) of 7 or less is preferred, and -OH, -COOH, -SO 3 H.-OSO 3 H, -PO 3 H 2 ,-OPO 3 H 2 、-CONHSO 2 、-SO 2 NHSO 2 -, and -COOH is particularly preferred. The presence of these acid groups (preferably carboxyl groups) can effectively improve the solubility of the alkali-soluble polymer in a low-concentration developer.

[0096] The polymerized unit containing an acid group (eg, carboxyl group) is not particularly limited as long as it contains an acid group in a side chain, but is preferably a polymerized unit derived from an unsaturated carboxylic acid, an unsaturated carboxylic anhydride, or a mixture thereof.

[0097] The polymerized unit containing an alkoxysilyl group may be a polymerized unit containing an alkoxysilyl group in a side chain, and is preferably a polymerized unit derived from a monomer represented by the following formula (B).

[0098] X B -(CH 2 ) a -Si(OR B ) b (CH 3 ) 3-b (B)

[0099] Where, X B is vinyl, styryl or (meth)acryloyloxy, R B is a methyl group or an ethyl group, a is an integer of 0 to 3, and b is an integer of 1 to 3.

[0100] Furthermore, the above-mentioned polymer preferably contains a hydroxyl group-containing polymerized unit derived from a hydroxyl group-containing unsaturated monomer.

[0101] The mass average molecular weight of the alkali-soluble polymer (preferably an acrylic polymer) of the present invention is not particularly limited, but is preferably 1,000 to 40,000, and more preferably 2,000 to 30,000. Here, the mass average molecular weight refers to the styrene-equivalent mass average molecular weight measured by gel permeation chromatography. In addition, with respect to the number of acid groups, from the viewpoint of being able to develop in a low-concentration alkaline developer and taking into account both reactivity and storage properties, the acid value of the solid content is usually 40 to 190 mgKOH / g, and more preferably 60 to 150 mgKOH / g.

[0102] In addition, when the composition of the present invention is a photosensitive composition, a cured film can be formed by coating on a substrate, exposing and developing. In this case, there must be a difference in solubility between the exposed portion and the unexposed portion, and the coating film of the unexposed portion should have a certain degree of solubility in the developer. For example, the dissolution rate of the pre-baked coating film in a 2.38 mass % KOH aqueous solution (hereinafter sometimes referred to as the alkali dissolution rate or ADR; described in detail later) is as long as If the above is considered, it is believed that a pattern can be formed by exposure and development. However, since the required solubility varies depending on the average film thickness of the cured film formed and the development conditions, the alkali-soluble polymer should be appropriately selected according to the development conditions. Although it varies depending on the type or amount of the photosensitizer or silanol condensation catalyst contained in the composition, for example, as long as the average film thickness is 0.1 to 100 μm The dissolution rate of 2.38% KOH aqueous solution is preferably More preferably

[0103] The polysiloxane and acrylic polymer used in the present invention are not particularly limited, and for example, the polysiloxane and acrylic polymer described in WO2021 / 018927A1 can be appropriately used.

[0104] The alkali-soluble polymer may be a single type or a mixture of two or more types. A combination of an acrylic polymer and a polysiloxane, two or more types of acrylic polymers, two or more types of polysiloxanes, etc. may also be used.

[0105] In a preferred embodiment, from the viewpoint of being able to form a film and a cured film at low temperature, the alkali-soluble polymer used in the present invention is a mixture of one or more acrylic polymers, and more preferably two acrylic polymers. More preferably, the alkali-soluble polymer is preferably selected from two acrylic polymers as follows: soluble in an organic solvent such as PGMEA, water-soluble, and soluble in an alkaline developer before exposure; more preferably, both of the two acrylic polymers have a structural part having an acid group, and more preferably, a polymer obtained by copolymerizing a structural part having an acid group and a structural part not having an acid group.

[0106] Here, as the acid group, an acid group having an acid dissociation constant (pKa) of 7 or less is preferred, and -OH, -COOH, -SO 3 H.-OSO 3 H, -PO 3 H 2 ,-OPO 3 H 2 、-CONHSO 2 、-SO 2 NHSO 2 -, particularly preferably -COOH.

[0107] The content of the component (I) is preferably 5 to 99.9% by mass, more preferably 70 to 90% by mass, based on the total mass of the composition excluding the solvent.

[0108] (II) Fluorinated compound having a crosslinking group

[0109] The composition of the present invention contains (II) a fluorine-containing compound having a crosslinking group. The component (II) is preferably a fluorine-containing surfactant having a crosslinking group.

[0110] The crosslinking group of the component (II) is preferably an epoxy group or an ethylenically unsaturated group, and more preferably an ethylenically unsaturated group.

[0111] The component (II) preferably has a perfluoroalkyl group or a perfluoroalkylene chain, and may have both. By having these groups, the oleophobicity of the upper portion of the formed film can be improved.

[0112] Examples of the perfluoroalkyl group include perfluorobutyl, perfluorohexyl, and perfluorooctyl. Examples of the perfluoroalkylene ether chain include -CF 2 -O-、-(CF 2 ) 2 -O-、-(CF 2 ) 3 -O-, -CF 2 -C(CF 3 )O-、-C(CF 3 )-CF 2 -O-, and a divalent group having these repeating units.

[0113] Specific examples of component (II) include, for example, acrylic copolymers having epoxy groups and perfluoroalkyl groups, acrylic copolymers having epoxy groups and perfluoroalkylene ether chains, acrylic copolymers having ethylenically unsaturated groups and perfluoroalkyl groups, acrylic copolymers having ethylenically unsaturated groups and perfluoroalkyl groups, epoxy (meth) acrylate polymers having epoxy groups and perfluoroalkyl groups, epoxy (meth) acrylate polymers having epoxy groups and perfluoroalkylene ether chains, epoxy (meth) acrylate polymers having ethylenically unsaturated groups and perfluoroalkyl groups, epoxy (meth) acrylate polymers having ethylenically unsaturated groups and perfluoroalkyl groups, and epoxy (meth) acrylate polymers having ethylenically unsaturated groups and perfluoroalkyl groups. Preferred are acrylic copolymers having ethylenically unsaturated groups and perfluoroalkyl groups, more preferably acrylic copolymers having ethylenically unsaturated groups and perfluoroalkylene ether chains, and still more preferably acrylic copolymers having ethylenically unsaturated groups and perfluoroalkylene ether chains. Examples of commercially available products of the acrylic copolymer having an ethylenically unsaturated group and a perfluoroalkylene ether chain include "MEGAFACE RS-72-K", "MEGAFACE RS-78", and "MEGAFACE RS-90".

[0114] The content ratio of fluorine atoms in the compound in the component (II) is not particularly limited, but is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and still more preferably 25 to 35% by mass.

[0115] The molecular weight of the component (II) is not particularly limited, but a high molecular weight is preferred because the fluidity due to baking is suppressed and outflow from the film can be suppressed, and the number average molecular weight is preferably 100 to 100,000, more preferably 500 to 10,000.

[0116] It is known that fluorinated surfactants are generally added to compositions for the purpose of improving coating properties and imparting hydrophobicity and oleophobicity to the surface of a coating film.

[0117] One of the characteristics of the amount of component (II) in the present invention is that it is added in an extremely small amount compared to the amount usually added for the above purpose.

[0118] By mixing with such a small amount, it can be achieved that the upper part of the formed film (preferably the partition wall) has oleophobicity, and the bottom or the side of the opening of the formed film (preferably the partition wall) has oleophilicity. Thus, for example, when forming a partition wall, the top of the partition wall can be ink-repellent to the quantum dot ink to prevent color mixing, while on the other hand, the area near the opening of the partition wall is ink-philic to efficiently bury the ink.

[0119] Although not limited to theory, it is believed that the following reasons are responsible. Since the composition of the present invention contains a very small amount of component (II), when forming a film, component (II) only gathers on the surface layer of the upper part of the film and undergoes cross-linking reaction with other components, so that a lyophobic part can be efficiently and effectively formed only on the uppermost surface, and a lyophilic part can be formed on the side and opening. Moreover, after the cured film is formed, component (II) is inhibited from moving and eluting.

[0120] Furthermore, environmentally friendly compositions have been sought in recent years, and the fact that the component (II) can exert its effect in an extremely small amount is also a great advantage from the viewpoint of environmental impact.

[0121] Preferably, in the present invention, "partition wall" refers to a partition wall or a black matrix arranged between each display pixel of the optical display device to divide the display pixel, such as the partition wall or black matrix described in JP2021-075660A, WO2017-138607A1, and JP2018-203599A.

[0122] The mass ratio of the content of component (II) to the content of component (I) ((II) / (I)) is 0.0000005 to 0.01, preferably 0.00001 to 0.005, and more preferably 0.00003 to 0.004. From the viewpoint of the most suitable surface free energy, the oleophobicity of the upper part of the formed film (preferably the partition wall), and the oleophilicity of the bottom or side part of the opening of the formed film (preferably the partition wall), it is further desired to be in the range of 0.0001 to 0.0035.

[0123] (III) Colorants

[0124] The composition of the present invention may further comprise (III) a colorant. Preferably, the (III) colorant is an organic colorant and / or an inorganic colorant. In a preferred embodiment, the (III) component comprises an organic and / or inorganic black colorant, more preferably an organic black colorant, further preferably a black colorant consisting of a mixture of two or more organic colorants, and even more preferably a mixture of red and blue-green organic colorants that exhibit black color after mixing.

[0125] When the black colorant used in the present invention is an organic colorant or pigment, it is preferable to combine two or more organic colorants or pigments. A black color material can be formed by mixing red, green, blue, and other colors.

[0126] Organic colorants and pigments are selected from, for example, substances having structures such as azo, phthalocyanine, quinacridone, benzimidazolone, isoindolinone, dioxazine, indanthrene, and perylene. As a preferred combination of pigments, for example, a combination of one or more selected from the group consisting of CI Pigment Orange 43, CI Pigment Orange 64, and CI Pigment Orange 72 and one or more selected from the group consisting of CI Pigment Blue 60, CI Pigment Green 7, CI Pigment Green 36, and CI Pigment Green 58 can be cited; more preferably, a combination of one selected from the group consisting of CI Pigment Orange 43, CI Pigment Orange 64, and CI Pigment Orange 72 and CI Pigment Blue 60. In this combination, other organic pigments may be further combined.

[0127] The content of the component (III) is preferably 1 to 80% by mass, more preferably 3 to 30% by mass, and even more preferably 5 to 10% by mass, based on the total mass of the component (I).

[0128] The content of the colorant is based on the mass of the pigment itself. That is, the colorant may be obtained in a dispersed state using a dispersant, but in this case, the mass of the colorant does not include substances other than the pigment.

[0129] The colorant used in the present invention may be used in combination with a dispersant. As the dispersant, for example, an organic compound-based dispersant such as a polymer dispersant described in Japanese Unexamined Patent Publication No. 2004-292672 may be used.

[0130] (IV) Polymerization initiator

[0131] The composition of the present invention may further contain a polymerization initiator. The polymerization initiator is a polymerization initiator that generates acid, base or free radicals by radiation, and a polymerization initiator that generates acid, base or free radicals by heat. In the present invention, since the reaction starts immediately after irradiation with radiation, the reheating process performed after irradiation with radiation and before the development process can be omitted, so in terms of process shortening and cost, the former is preferred, and the photo free radical generator is more preferred.

[0132] The photoradical generator can improve the resolution by reinforcing the shape of the pattern and increasing the contrast of the development. The photoradical generator used in the present invention is a photoradical generator that releases free radicals when irradiated with radiation. Here, as radiation, visible light, ultraviolet light, infrared light, X-rays, electron beams, α rays, or γ rays can be listed.

[0133] The optimum amount of the photoradical generator varies depending on the type of active substances generated by the decomposition of the photoradical generator, the amount generated, the required sensitivity, and the dissolution contrast between the exposed and unexposed parts, but is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, based on the total mass of the component (I). From the viewpoint of ensuring sufficient dissolution contrast between the exposed and unexposed parts and exerting the effect of addition, the added amount is preferably 0.1% by mass or more. On the other hand, in order to prevent cracks from forming in the formed film, prevent the colorless transparency of the film from being reduced due to obvious coloration caused by the decomposition of the photoradical generator, prevent the deterioration of the electrical insulation of the cured product due to thermal decomposition of the photoradical generator, and prevent gas release, which may cause problems in subsequent steps, and further prevent the film from being reduced in resistance to photoresist stripping solutions containing monoethanolamine as a main agent, etc., from these viewpoints, the added amount of the photoradical generator is preferably less than 50% by mass.

[0134] In order to obtain the optimal curing conditions, it is preferred to adjust the amount of the photoradical generator according to the heating temperature (curing temperature) in the post-exposure heating step.

[0135] Examples of photoradical generators include azo, peroxide, acylphosphine oxide, alkylphenone, oxime ester, and titanocene initiators. Among them, alkylphenone, acylphosphine oxide, and oxime ester initiators are preferred, and examples thereof include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one. , 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetyl oxime), etc.

[0136] (V) Solvent

[0137] The composition of the present invention may further contain (V) a solvent. The solvent is not particularly limited as long as it is a solvent that uniformly dissolves or disperses the aforementioned components and the components added as needed. Examples of solvents that can be used in the present invention include ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; ethylene glycol alkyl ether acetates such as methyl cellosolve acetate and ethyl cellosolve acetate; propylene glycol such as propylene glycol monomethyl ether and propylene glycol monoethyl ether. Monoalkyl ethers; propylene glycol alkyl ether acetates such as PGMEA, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate; aromatic hydrocarbons such as benzene, toluene, and xylene; ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone; alcohols such as ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, and glycerol; esters such as ethyl lactate, ethyl 3-ethoxypropionate, and methyl 3-methoxypropionate; and cyclic esters such as γ-butyrolactone. Among these, PGMEA is preferably used from the viewpoints of ease of acquisition, ease of handling, and solubility in alkali-soluble materials.

[0138] The solvent content of the composition of the present invention can be arbitrarily adjusted according to the method of applying the composition, etc. For example, when the composition is applied by spraying, the ratio of the solvent in the composition can be adjusted to 90% by mass or more. In addition, in the slit coating used when applying to a large substrate, it is usually 60% by mass or more, preferably 70% by mass or more. The characteristics of the composition of the present invention will not change much with the amount of solvent.

[0139] (VI) Cross-linking agent

[0140] The composition of the present invention may further contain (VI) a crosslinking agent. Component (VI) is different from components (I) and (II).

[0141] Examples of the crosslinking agent include melamine compounds, isocyanate compounds, and thiol compounds having a methylol group, an alkoxymethyl group, and the like.

[0142] Specific examples of the cross-linking agent include NIKALAC MW-390, NIKALAC MW-100LM, NIKALAC MX-750LM, NIKALAC MX-270, and NIKALAC MX-280 having an imino group, a methylol group, a methoxymethyl group, and the like.

[0143] Examples of the isocyanate compound include X-12-9659, KBM-9659, and X-12-9659, or KBM-585 (Shin-Etsu Chemical Co., Ltd.).

[0144] In addition, polymers containing these structures or polymers in which a part of these structures is replaced by a silicone group are also preferred. In addition to silane compounds, Karenz AOI, Karenz MOI-BM, Karenz MOI-BP, Karenz BEI, Karenz MT (Showa Denko K.K.), hexamethylene diisocyanate, cyclohexane diisocyanate, etc. can be cited. In one embodiment of the present invention, the crosslinking agent is a thiol compound.

[0145] The content of the crosslinking agent is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, relative to the total mass of component (I). The crosslinking agent can be used alone or in combination of two or more. By making the content of the crosslinking agent within the above range, for example, the crosslinking reaction of the crosslinking agent can be improved in a low temperature region of about 80°C to 95°C, and further, the amount of component (II) used can be reduced, thereby obtaining a more environmentally friendly cured film having the desired properties.

[0146] (VII) Additives

[0147] The composition of the present invention may contain (VII) additives other than the above-described components as required. Such additives are at least one of a developer dissolution promoter, a scum remover, a close contact enhancer, a polymerization inhibitor, a defoamer, a surfactant different from (II), a sensitizer, a curing agent, or a mixture thereof.

[0148] The content of the (VII) additive is preferably 3% by mass or less, more preferably 1% by mass or less, based on the total mass of the composition excluding the solvent. In a preferred embodiment, the (VI) additive is not contained, that is, the content is 0% by mass.

[0149] <Method for producing cured film>

[0150] The method for producing a cured film of the present invention comprises a coating step of coating the composition described above on a substrate to form a coating film; and a step of heating the coating film.

[0151] The method for producing a cured film preferably further comprises a step of exposing the coating film; and a step of developing the coating film. More preferably, the method for producing a cured film of the present invention sequentially comprises: a step of applying the aforementioned composition to a substrate to form a coating film; a step of exposing the coating film; a step of developing the coating film; and a step of heating the coating film; and more preferably, a pre-baking step is included after the aforementioned coating step and before the exposure step.

[0152] The method for producing a cured film of the present invention will be described below in order of steps.

[0153] (1) Coating process

[0154] First, the aforementioned composition is coated on a substrate. The formation of the coating film of the composition of the present invention can be carried out by any method known in the past as a coating method of a photosensitive composition. Specifically, it can be arbitrarily selected from dip coating, roller coating, rod coating, brush coating, spray coating, blade coating, flow coating, spin coating, and slit coating, etc. In addition, as the base material of the coating composition, suitable base materials such as silicon substrates, glass substrates, and resin films can be used. In these base materials, various semiconductor elements, etc. can also be formed as needed. In the case where the base material is a film, gravure coating can also be utilized. As needed, a drying process can also be set separately after the coating film. In addition, as needed, the coating process can be repeated 1 or more times to make the film thickness of the formed coating film become the desired film thickness.

[0155] (2) Pre-baking process

[0156] After forming a coating film by applying the coating composition, in order to dry the coating film and reduce the amount of solvent residue in the coating film, the coating film is preferably pre-baked (pre-heat treated). The pre-baking process is usually carried out at a temperature of 40 to 150° C. (preferably 50 to 100° C.), and can be carried out for 10 to 300 seconds, preferably 30 to 120 seconds, when using a hot plate, and can be carried out for 1 to 30 minutes when using a clean oven.

[0157] (3) Exposure process

[0158] After the coating is formed, the coating surface is irradiated with light as desired. The light source used for light irradiation can be any light source used in the pattern forming method in the past. Examples of such light sources include high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, xenon lamps, or laser diodes, LEDs, etc. As irradiation light, ultraviolet rays such as g-rays, h-rays, and i-rays can usually be used. In addition to ultra-fine processing such as semiconductors, 360-430nm light (high-pressure mercury lamps) is generally used for patterning of several μm to tens of μm. The energy of the irradiation light also varies depending on the light source or the film thickness of the coating, and is generally 1 to 1000mJ / cm 2 , preferably 5 to 500 mJ / cm 2 , more preferably 10 to 300 mJ / cm 2 From the perspective of obtaining sufficient resolution, the irradiation light energy is preferably higher than 5 mJ / cm 2 From the perspective of preventing excessive exposure and halation, the irradiation light energy is preferably 500 mJ / cm 2 the following.

[0159] In order to irradiate light into a pattern shape, a common photomask can be used. Such a photomask can be arbitrarily selected from known photomasks. The environment during irradiation is not particularly limited, and usually it only needs to be the surrounding atmosphere (in the air) or a nitrogen atmosphere. In addition, in the case of forming a film on the entire surface of the substrate, it is sufficient to irradiate the entire surface of the substrate with light. In the present invention, the pattern film also includes the case where a film is formed on the entire surface of such a substrate.

[0160] (4) Post-exposure heating process

[0161] After exposure, in order to promote the reaction between polymers in the film by the reaction initiator generated in the exposed part, post-exposure heating may be performed as needed. This heating treatment is different from the heating step (6) described later. It is not performed to completely cure the coating film, but is performed to leave only the desired pattern on the substrate after development, and the rest can be removed by development. Therefore, it is not necessary in the present invention.

[0162] In the case of heating after exposure, a hot plate, an oven, or a heating furnace can be used. Since it is not preferred that the acid in the exposure area generated by light irradiation diffuses to the unexposed area, the heating temperature should not be too high. From this point of view, the range of the heating temperature after exposure is preferably 40°C to 150°C, and more preferably 60°C to 120°C. In order to control the curing rate of the composition, staged heating can also be appropriately adopted as needed. In addition, the atmosphere during heating is not particularly limited, and for the purpose of controlling the curing rate of the composition, it can be selected from inert gases such as nitrogen, vacuum, reduced pressure, oxygen, etc. In addition, in order to maintain a higher uniformity in the temperature history within the wafer surface, the heating time is preferably more than a certain time, and in order to suppress the diffusion of the generated acid, it is preferably not too long. From this point of view, the heating time is preferably 20 seconds to 500 seconds, and more preferably 40 seconds to 300 seconds.

[0163] (5) Development process

[0164] After exposure, the coating film is subjected to development treatment after post-exposure heating as needed. As the developer used in development, any developer used in the development of the photosensitive composition in the past can be used. As preferred developers, alkaline developers of aqueous solutions of alkaline compounds such as tetraalkylammonium hydroxide, choline, alkali metal hydroxides, alkali metal metasilicates (hydrates), alkali metal phosphates (hydrates), sodium carbonate aqueous solutions, ammonia, alkylamines, alkanolamines, and heterocyclic amines can be listed, and particularly preferred alkaline developers are tetramethylammonium hydroxide aqueous solutions, potassium hydroxide aqueous solutions, or sodium hydroxide aqueous solutions, sodium carbonate aqueous solutions. In these alkaline developers, water-soluble organic solvents such as methanol and ethanol, or surfactants can also be further included as needed. In the present invention, a developer with a lower concentration than the 2.38 mass % TMAH developer used as a normal developer can be used for development. As such a developer, for example, 0.05-1.5 mass % TMAH aqueous solutions, 0.1-2.5 mass % sodium carbonate aqueous solutions, 0.01-1.5 mass % potassium hydroxide aqueous solutions, etc. can be listed. The developing time is usually 10 to 300 seconds, preferably 30 to 180 seconds. The developing method can also be selected from any of the conventionally known methods. Specifically, methods such as dipping, immersion, spraying, slit, cap coating, and spraying can be cited. A pattern can be obtained by this development; after development with the developer, it is preferably washed with water.

[0165] (6) Heating process

[0166] The coating is cured by heating. The heating device used in the heating process can use the same device as the device used in the above-mentioned post-exposure heating. As the heating temperature in the heating process, as long as it is a temperature at which the coating can be cured, it is not particularly limited and can be set arbitrarily. However, in the case of using polysiloxane, if the silanol group in the polysiloxane remains, the chemical resistance of the cured film will become insufficient and the dielectric constant of the cured film will become higher. From this point of view, a relatively high temperature is usually selected for the heating temperature. However, the composition of the present invention can be cured at a relatively low temperature. Specifically, it is preferably heated below 350°C to cure it. In order to maintain a high residual film rate after curing, the curing temperature is preferably below 300°C, and particularly preferably below 250°C. On the other hand, in order to promote the curing reaction and obtain a sufficient cured film, the curing temperature is preferably above 70°C, and more preferably above 80°C. In addition, the heating time is not particularly limited, and is usually 10 minutes to 24 hours, preferably 20 minutes to 3 hours. It should be noted that the heating time is the time calculated after the temperature of the pattern film reaches the desired heating temperature. Generally, it takes about several minutes to several hours for the pattern film to reach a desired temperature from the temperature before heating.

[0167] The cured film thus formed can exhibit the effects of the present application as long as the average film thickness is 100 μm or less, and is preferably 0.1 to 100 μm, more preferably 5 to 25 μm, and even more preferably 8 to 20 μm.

[0168] The optical density (OD) of the cured film is preferably 1.5 or more, more preferably 2 or more, at a wavelength of 400 to 700 nm. The optical density can be measured by Spectrophotometer CM-5 (Konica Minolta). In a preferred embodiment, the OD at each of wavelengths of 460 nm, 540 nm, and 630 nm is preferably 1.5 or more, more preferably 2 or more.

[0169] The cured film of the present invention has excellent light shielding properties and can be used as a partition material for display devices. Since the cured film of the present invention can be thickened, it can be suitably used in quantum dots and organic light-emitting devices that require thicker partition materials.

[0170] In another aspect, the present invention relates to a cured film produced by the above method or producible by the method.

[0171] In another aspect, the present invention relates to a cured film comprising an alkali-soluble material and a polymer derived from a fluorine-containing compound having a crosslinking group.

[0172] The cured film is preferably patterned, and more preferably is a patterned partition wall.

[0173] It is preferred that the cured film further contains a colorant. It is more preferred that the colorant is an organic colorant and / or an inorganic colorant, and it is further preferred that the colorant contains an organic and / or inorganic black colorant.

[0174] In another aspect, the present invention relates to a photoconversion device including a cured film.

[0175] In another aspect, the present invention relates to a display device including a cured film or a photoconversion device.

[0176] Preferred embodiments are listed below.

[0177] [Implementation 1]

[0178] A composition comprising (I) an alkali-soluble material, and (II) a fluorine-containing compound having a cross-linking group;

[0179] The mass ratio of the content of component (II) to the content of component (I) ((II) / (I)) is 0.0000005 to 0.01. Preferably, it is 0.00001 to 0.005, and more preferably, it is 0.00003 to 0.004. From the viewpoint of the optimum surface free energy, the oleophobicity of the upper part of the formed film (preferably the partition wall), and the oleophilicity of the bottom or side part of the opening of the formed film (preferably the partition wall), it is more preferably in the range of 0.0001 to 0.0035.

[0180] Preferably, the composition is a cured film-forming composition.

[0181] The composition is preferably a photosensitive composition, and more preferably a negative-type photosensitive composition.

[0182] Preferably the composition further comprises:

[0183] (III) a colorant, preferably an organic colorant and / or an inorganic colorant, and more preferably the colorant comprises an organic and / or inorganic black colorant;

[0184] (IV) a polymerization initiator; and / or

[0185] (V) Solvent.

[0186] [Implementation 2]

[0187] The composition according to embodiment 1, wherein the crosslinking group is an epoxy group or an ethylenically unsaturated group, preferably an ethylenically unsaturated group.

[0188] [Implementation Plan 3]

[0189] The composition according to embodiment 1 or 2, wherein the aforementioned fluorinated surfactant having a crosslinking group has a perfluoroalkyl or perfluoroalkylene chain, preferably the perfluoroalkyl is selected from the group consisting of perfluorobutyl, perfluorohexyl, and perfluorooctyl, and the perfluoroalkylene ether chain is selected from -CF 2 -O-、-(CF 2 ) 2 -O-、-(CF 2 ) 3 -O-, -CF 2 -C(CF 3 )O-、-C(CF 3 )-CF 2 -O-, and a divalent group having these repeating units.

[0190] The fluorinated surfactant having a crosslinking group preferably has an ethylenically unsaturated group and a perfluoroalkylene ether chain.

[0191] [Implementation 4]

[0192] The composition according to any one of Embodiments 1 to 3, wherein (I) the alkali-soluble material is a compound containing two or more (meth)acryloyloxy groups and / or an alkali-soluble polymer.

[0193] The compound containing two or more (meth)acryloyloxy groups is preferably an ester obtained by reacting (α) a polyol compound having two or more hydroxyl groups with (β) two or more (meth)acrylic acids.

[0194] The (α) polyol compound is preferably a compound having a saturated or unsaturated aliphatic hydrocarbon, aromatic hydrocarbon, heterocyclic hydrocarbon, primary amine, secondary amine, tertiary amine, ether or the like as a basic skeleton and having two or more hydroxyl groups as substituents.

[0195] It is preferred that the (α) polyol compound further contains one or more substituents selected from the group consisting of a carboxyl group, a carbonyl group, an amino group, an ether bond, a thiol group, and a thioether bond.

[0196] It is preferred that the (α) polyol compound is selected from the group consisting of alkyl polyols, aryl polyols, polyalkanolamines, cyanuric acid, and dipentaerythritol.

[0197] Preferred are tris(2-acryloyloxyethyl)isocyanurate, dipentaerythritol hexaacrylate, or a combination thereof.

[0198] More preferred is a combination of a compound containing three (meth)acryloyloxy groups and a compound containing two (meth)acryloyloxy groups.

[0199] The molecular weight of the compound containing two or more (meth)acryloyloxy groups is preferably 2,000 or less, more preferably 1,500 or less.

[0200] The content of the compound having two or more (meth)acryloyloxy groups is preferably 5 to 90% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 70% by mass, based on the total mass of the composition excluding the solvent.

[0201] Preferably, the alkali-soluble polymer is selected from the group consisting of (meth)acrylic polymers, silicone polymers, silicone (meth)acrylic polymers, and mixtures thereof.

[0202] The alkali dissolution rate of the alkali-soluble polymer was measured and calculated as follows using a 0.03 mass % KOH aqueous solution as an alkali solution.

[0203] The alkali-soluble polymer was diluted to 35% by mass in PGMEA and dissolved by stirring for 1 hour at room temperature using a stirrer. In a clean room at a temperature of 23.0±0.5°C and a humidity of 50±5.0%, 1cc of the modulated alkali-soluble polymer solution was dropped onto the center of a 4-inch, 525μm thick silicon wafer using a pipette and spin-coated to a thickness of 2±0.1μm, and then heated on a hot plate at 100°C for 90 seconds to remove the solvent. The film thickness of the coating was measured using a spectroscopic ellipsometer (JA Woollam).

[0204] Next, the silicon wafer with the film is quietly immersed in a 6-inch diameter glass petri dish adjusted to 23.0±0.1°C and filled with 100 ml of 0.03% KOH aqueous solution, and then allowed to stand to measure the time until the coating disappears. The dissolution rate is calculated by dividing the time until the film disappears from the end of the wafer 10 mm inward. In the case where the dissolution rate is significantly slow, the film thickness is measured after the wafer is immersed in the KOH aqueous solution for a certain period of time, and the change in film thickness before and after immersion is divided by the immersion time to calculate the dissolution rate. The above measurement method is performed 5 times, and the average value of the obtained values ​​is used as the dissolution rate of the alkali-soluble polymer.

[0205] The alkali-soluble polymer is preferably a polymer that, in the measurement and calculation of the alkali dissolution rate, dissolves and disappears in a 0.03% KOH aqueous solution within 10 minutes at a coating film 10 mm inward from the wafer edge.

[0206] [Implementation 5]

[0207] The composition according to any one of Embodiments 1 to 4, wherein (I) the alkali-soluble material comprises a compound having two or more (meth)acryloyloxy groups.

[0208] [Implementation Plan 6]

[0209] The composition according to Embodiment 5, wherein (I) the alkali-soluble material further comprises an alkali-soluble polymer.

[0210] The content of the compound containing two or more (meth)acryloyloxy groups is preferably 10 to 95% by mass, more preferably 30 to 90% by mass, and even more preferably 50 to 80% by mass based on the total mass of the component (I).

[0211] [Implementation Plan 7]

[0212] The composition according to any one of embodiments 1 to 6, further comprising (III) a colorant.

[0213] Preferably, the colorant (III) is an organic and / or inorganic black colorant, more preferably an organic black colorant; further preferably a black colorant consisting of a mixture of two or more organic colorants; and further more preferably a mixture of red and blue-green organic colorants that appear black after mixing.

[0214] The content of the colorant (III) is preferably 3 to 80% by mass, more preferably 5 to 50% by mass, based on the total mass of the component (I).

[0215] [Implementation Plan 8]

[0216] The composition according to any one of Embodiments 1 to 7, further comprising (IV) a polymerization initiator.

[0217] The polymerization initiator is preferably a photoradical generator.

[0218] The content of the photoradical generator is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, based on the total mass of the component (I).

[0219] [Implementation Plan 9]

[0220] The composition according to any one of embodiments 1 to 8, further comprising (VI) a solvent.

[0221] Preferably, the solvent (VI) is ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether and ethylene glycol monobutyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether and diethylene glycol dibutyl ether; ethylene glycol alkyl ether acetates such as methyl cellosolve acetate and ethyl cellosolve acetate; propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether and propylene glycol monoethyl ether; PGM Propylene glycol alkyl ether acetates such as EA, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate; aromatic hydrocarbons such as benzene, toluene and xylene; ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone; alcohols such as ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol and glycerol; esters such as ethyl lactate, ethyl 3-ethoxypropionate and methyl 3-methoxypropionate; and a combination of one or more of cyclic esters such as γ-butyrolactone.

[0222] The composition of the present invention preferably further comprises (VI) a cross-linking agent, more preferably a thiol compound.

[0223] The composition of the present invention preferably contains (VII) an additive. The content of the (VII) additive is preferably 3% by mass or less, more preferably 1% by mass or less, based on the total mass of the composition excluding the solvent.

[0224] [Implementation Plan 10]

[0225] A method for producing a cured film, comprising the steps of applying the composition according to any one of Embodiments 1 to 9 to a substrate to form a coating film; and heating the coating film.

[0226] The method for producing a cured film preferably further comprises the step of exposing the coating film; and the step of developing the coating film. More preferably, the method for producing a cured film comprises, in sequence: applying the composition described in any one of Embodiments 1 to 9 to a substrate to form a coating film; exposing the coating film; developing the coating film; and heating the coating film; and more preferably, a pre-baking step is further included after the coating step and before the exposure step.

[0227] [Implementation Plan 11]

[0228] A cured film produced by the method described in Embodiment 11 or producible by the method.

[0229] [Implementation Plan 12]

[0230] A cured film comprises an alkali-soluble material and a polymer derived from a fluorine-containing compound having a crosslinking group.

[0231] The cured film is preferably patterned, and more preferably the cured film is a patterned partition wall.

[0232] It is preferred that the cured film further contains a colorant. It is more preferred that the colorant is an organic colorant and / or an inorganic colorant, and it is further preferred that the colorant contains an organic and / or inorganic black colorant.

[0233] [Implementation Plan 13]

[0234] The cured film according to embodiment 11 or 12 has an average film thickness of 0.1 to 100 μm, preferably 1 to 50 μm, more preferably 1 to 25 μm, and further preferably 5 to 20 μm.

[0235] [Implementation Plan 14]

[0236] The cured film according to any one of Embodiments 11 to 13, wherein the upper portion of the cured film is oleophobic and the lower portion is oleophilic. The cured film is preferably patterned, and more preferably the cured film is a patterned partition wall.

[0237] [Implementation Plan 15]

[0238] A photoconversion device comprising the cured film according to any one of Embodiments 11 to 14.

[0239] [Implementation Plan 16]

[0240] A display device comprising the cured film according to any one of Embodiments 11 to 14, or the photoconversion device according to Embodiment 15.

[0241] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples.

[0242] <Example 1>

[0243] To 100 parts by mass of a PGMEA solution containing a mixture of acrylic polymer A (Shin-Nakamura Chemical Industry Co., Ltd.) and acrylic polymer B (Natoco Co., Ltd.) at a mass ratio of 3:1, 3.1 parts by mass of polymerization initiator A (ADEKA Co., Ltd.) and polymerization initiator B (IGM Resins BV), 170 parts by mass of a (meth)acryloyloxy-containing compound A (Shin-Nakamura Chemical Industry Co., Ltd.), 20 parts by mass of a crosslinking agent A (Showa Denko K.K.), 15 parts by mass of a colorant A (Toyocolor Co., Ltd.), 1.9 parts by mass of a colorant B (Hayashibara Co., Ltd.), 1.7 parts by mass of a colorant C (Hayashibara Co., Ltd.), 2.2 parts by mass of a colorant D (Hayashibara Co., Ltd.) and 0.6 parts by mass of a fluorinated surfactant A having a crosslinking group (DIC Corporation) were added, and PGMEA was added to prepare a solution having a solid content ratio of 35% by mass, thereby obtaining the composition of Example 1.

[0244] <Examples 2 to 12 and Comparative Example 1>

[0245] Except having changed into the composition shown in Table 1, it carried out similarly to Example 1, and prepared the composition of Examples 2-12 and Comparative Example 1.

[0246]

[0247] In the table,

[0248] (Meth)acryloyloxy-containing compound A: dipentaerythritol hexaacrylate "A-DPH", Shin-Nakamura Chemical Industry Co., Ltd.;

[0249] Acrylic polymer A: an acrylic random polymer made from a carboxylic acid monomer and a monomer containing at least one aromatic ring group, Shin-Nakamura Chemical Industry Co., Ltd.;

[0250] Acrylic polymer B: 2-acrylic acid, 2-methyl-, and a polymer having 2-hydroxyethyl 2-methyl-2-acrylate, 2-isocyanatoethyl 2-acrylate and 2-methyl-2-methyl methyl ester, Natoco Co., Ltd.;

[0251] Fluorine-containing compound A having a crosslinking group: "RS-90", DIC Corporation;

[0252] Fluorine-containing compound B having a crosslinking group: "RS-72-A", DIC Corporation;

[0253] Colorant A: black colorant, Toyocolor Co., Ltd.

[0254] Colorant B: anthocyanin pigment, Hayashibara Co., Ltd.;

[0255] Colorant C: anthocyanin pigment, Hayashibara Co., Ltd.;

[0256] Colorant D: Coumarin pigment, Hayashihara Co., Ltd.;

[0257] Polymerization initiator A: "NCI-831", ADEKA Corporation;

[0258] Polymerization initiator B: “Omnirad784”, IGM Resins BV;

[0259] Crosslinking agent A: thiol compound "Karenz MT PE-1", Showa Denko K.K.

[0260] (Pattern making)

[0261] Each of the obtained compositions was applied on a glass substrate by spin coating (MS-A100, MIKASA), and after coating, it was pre-baked at 60°C for 90 seconds on a hot plate (HHP-411V, AS ONE) to adjust the average film thickness to 10μm. An i-ray exposure machine (NES2W-ghi06, Nikon) was used for exposure, and 0.03 mass% KOH was used as a developer to produce a 150×150μm hole pattern. The patterned substrate was placed in an oven at 85°C (DP-200, Yamato) and heated for 30 minutes to promote curing. The pattern was confirmed to be free of residue using an optical microscope (MX61A, OLYMPUS) and SEM (JSM-7100, JEOL). The results obtained are recorded in Table 1.

[0262] (Optical density measurement)

[0263] In order to measure the optical density, a substrate without pattern was prepared. In the exposure process, a photomask was not used, and the entire surface of the substrate was exposed. The other processes were made in the same order as the pattern production. The light transmission spectrum was measured with a spectrophotometer (CM-5, KONICA MINOLTA), and the OD values ​​of wavelengths 460nm, 540nm, and 650nm were calculated. The results are shown in Table 1.

[0264] (Surface free energy determination)

[0265] In order to measure the surface free energy, a substrate without pattern is prepared. In the exposure process, the entire surface of the substrate is exposed without using a photomask. The other processes are carried out in the same order as the pattern production to produce a film. The produced substrate is mounted on a contact angle meter (DropMaster700, Kyowa) to measure the contact angle of distilled water and 3μL of diiodomethane. The surface free energy is calculated from the theoretical formula of Owens-Wendt and the obtained contact angle value. The results are recorded in Table 1.

[0266] (Ink production)

[0267] Ink A is prepared by mixing the materials described in the following Table 2. The ink can also be prepared using the materials and methods described in, for example, WO2021 / 116139A1.

[0268] Table 2

[0269] Green light emitting InP / ZnSe / ZnS QD 40.0% by mass LA+HDDA (LA:HDDA=80:20) monomer mixture 52.5% by mass <![CDATA[TiO 2 Particles (scattering particles)]]> 6% by mass Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Omnirad 819) 1.0% by mass Irganox 1010 0.5% by mass

[0270] In the table, the method for preparing the monomer mixture is as follows.

[0271] 1,6-Hexanediol diacrylate (HDDA) was passed through a molecular sieve before use to obtain a high-purity treatment. Then, 2 g of the high-purity treated HDDA and 8 g of lauryl acrylate (LA, viscosity: 4.0 cP, BP: 313.2° C.) were mixed in a glass vial at a ratio of (HDDA:LA=2:8) to obtain a monomer mixture.

[0272] (Ink diffusion test)

[0273] One drop (10 pl) of ink A was sprayed on a hole pattern of 150×150 μm by an inkjet printer (Dimatix DMP-2831, FujiFilm). The droplet size (length) was measured using an optical microscope (VK-X1000, KEYENCE) to evaluate the spread of the ink.

[0274] Similarly, one drop of ink A was dropped on the partition wall, and the spreading of the ink was evaluated.

[0275] The obtained results are shown in Table 1. The unit of the numerical value is μm.

Claims

1. A composition comprising (I) an alkali-soluble material, and (II) a fluorine-containing compound having a crosslinking group; in, The mass ratio (II) / (I) of the content of the component (II) to the content of the component (I) is 0.0000005 to 0.

01.

2. The composition according to claim 1, wherein The crosslinking group is an epoxy group or an ethylenically unsaturated group.

3. The composition according to claim 1 or 2, wherein The fluorine-containing compound having a crosslinking group has a perfluoroalkyl chain or a perfluoroalkylene chain.

4. The composition according to any one of claims 1 to 3, wherein (I) The alkali-soluble material is a compound containing two or more (meth)acryloyloxy groups and / or an alkali-soluble polymer.

5. The composition according to any one of claims 1 to 4, wherein (I) The alkali-soluble material includes a compound having two or more (meth)acryloyloxy groups.

6. The composition according to claim 5, wherein (I) The alkali-soluble material further includes an alkali-soluble polymer.

7. The composition according to any one of claims 1 to 6, further comprising (III) a colorant.

8. The composition according to any one of claims 1 to 7, further comprising (IV) a polymerization initiator. 9 . The composition according to claim 1 , further comprising (V) a solvent.

10. A method for producing a cured film, comprising: A step of applying the composition according to any one of claims 1 to 9 to a substrate to form a coating film; and A step of heating the coating film.

11. A cured film produced by the method according to claim 10 or capable of being produced by the method.

12. A cured film comprising an alkali-soluble material and a polymer derived from a fluorine-containing compound having a crosslinking group.

13. The cured film according to any one of claims 11 to 12, wherein The upper part of the cured film is oleophobic, and the lower part is oleophilic. 14 . A photoconversion device comprising the cured film according to claim 11 . 15 . A display device comprising the cured film according to claim 11 , or the photoconversion device according to claim 14 .

Citation Information

Patent Citations

  • Carbon black dispersion

    JP2004292672A

  • Zirconium nitride powder and manufacturing method therefor

    JP2018203599A

  • Pigment dispersion

    JP2021075660A

  • Organic electroluminescent element and organic electroluminescent display device

    WO2017138607A1

  • Negative type photosensitive composition comprising black colorant

    WO2021018927A1